Development of leisure and sports consumption and sports motivation among children with disabilities - Laoues-Czimbalmos, Nóra; Szerdahelyi, Zoltán; Müller , Anetta (Applied Studies in Agribusiness and Commerce, 2021)
The number of studies on the leisure and sporting habits of people with disabilities as well as the background of sports motivation is far from the focus of research on intact research. Thus, the assessment of physical habits and sports motivation factors determining the quality of life of persons with disabilities can be considered as a less researched deficit area in Hungary and internationally. In our research, we examine the recreational and sporting habits of the 8-18 year-olds, as well as the motivational background, and the results of this research are presented in this paper. The importance of this issue is confirmed by the fact that, according to a UN survey, 650 million people have some kind of disability, 50 million of them in Europe and nearly half a million in Hungary, 5% of the population. The questionnaire (N = 639) was filled by children with disabilities living in the North Great Plain region with the help of a teacher. We used both closed and open questions in the questionnaire, and we helped and orient children with response categories for some questions. Data were processed using SPSS software, averaged, standard deviation, median, mode, and Chi2 probe was used to examine relationships in addition to basic statistics. Our results showed that it is a problem for young people with disabilities that they prefer passive leisure activities, which is similar to the results of studies on intact research. Boys and girls have different sports, boys are more active than girls.